Penilaian Kinerja Keuangan Bank Bukopin Pendekatan Camel - Saifudin Saifudin; Ardiani Ika Sulistyawati; Natalia Debby Anggraini Putri (Jurnal Dinamika Ekonomi & Bisnis, 2021)
PT Bank Bukopin acquisition by KB Kookmin Bank make it necessary for the writer to analyze the financial performance of PT Bank Bukopin based on CAMELs principles. This study aims to find out the health level of PT Bank Bukopin in terms of capital, asset quality, management, earning, and liquidity.This study uses a descriptive quantitative method of case study, using secondary data from Indonesia Stock Exchange and processed by testing credibility and data narrative.From the results of PT Bank Bukopin research in 2017-2019 shows that finalcial performance by CAMELs principles in 2017 was categorized as unhealthy, in 2018 was categorized as unhealthy, and in 2019 was categorized as unhealthy.